Treponema pallidum protein Tp0136 promoting MMPs/TIMPs imbalance via PI3K, MAPK and NF-κB signalling pathways in HDVSMCs. Issue 12 (December 2022) - Cai, Chun-Xiang; Li, Shu-Lian; Lin, Hui-Ling; Wei, Zi-Han; Xie, Lin; Lin, Li-Rong; Niu, Jian-Jun; Yang, Tian-Ci
Abstract: The invasive capability of Treponema. pallidum is central to its infection process. Matrix metalloproteinases (MMPs), which are specifically inhibited by the tissue inhibitors of metalloproteinases (TIMPs), play a pivotal role in promoting pathogenic invasion by destroying tissue barriers within the body. This study aimed to explore the effect of T. pallidum protein Tp0136 on the balance of MMPs/TIMPs in human dermal vascular smooth muscle cells (HDVSMCs) and the related underlying mechanisms. A number of in vitro studies were conducted to access the impact of recombinant Tp0136 protein on the balance of MMPs/TIMPs in HDVSMCs. The involvement of the PI3K, MAPK, and NF-κB signaling pathways in this process was also investigated. Tp0136 induced the mRNA and protein expressions of MMP1 in HDVSMCs in a concentration-dependent way. In addition, MMP1/TIMP1 and MMP1/TIMP2 ratios were also increased. Furthermore, the study demonstrated that treatment of HDVSMCs with Tp0136 activated the PI3K, MAPK, and NF-κB signaling pathways. Inhibition of PI3K, JNK, P38, and NF-κB, suppressed MMP1 expression and reduced the induction of MMP1/TIMP1 and MMP1/TIMP2 ratios by Tp0136. These findings demonstrate that Tp0136 enhanced the expression of MMP1 involving the PI3K, MAPK, and NF-κB signaling pathways in HDVSMCs, and thus generated the unbalance of MMPs/TIMP, which could contribute to the early spread of T. pallidum and pathogenesis of syphilis. Abstract : Treponema pallidum ; Vascular smooth muscle cells; Matrix metalloproteinases; Tissue inhibitors of metalloproteinases, Imbalance.